Coronary Vasospasm: Cardiotoxic Effect of Platinum Based Monotherapy? - Chalaby, Shahad Al; Ahuja, Rahul; Barbant, Sophie (Cardiology and Cardiovascular Medicine, 2020)
We describe a case of a 61-year-old female presenting with recurrent episodes of acute dyspnea and found to have coronary artery vasospasm leading to variable wall motion abnormalities, myocardial infarction and fatal arrhythmias. The clinical presentation, differential diagnoses, diagnostic evaluation and treatment of cisplatin induced cardiotoxicity are discussed below. <gdiv></gdiv>